2000
DOI: 10.1021/ic000047l
|View full text |Cite
|
Sign up to set email alerts
|

Oxo/Sulfidotungstate(VI) as Precursors to WVIO2, WVIOS, and WVIS2 Complexes and WIV−Dithiolene Chelate Rings

Abstract: Synthetic models leading to oxosulfidotungsten(VI) groups and dithiolene chelate rings have been investigated. The heterogeneous reaction systems [WO4-nSn]2-/2Ph3SiCl/Me4phen (n = 0-2) in acetonitrile afford the complexes [WQ2(OSiPh3)2(Me4phen)] (1-3) in the indicated yields containing the groups W(VI)O2 (1; 86%), W(VI)O2 (2; 45%), and W(VI)S2 (3; 83%). In the crystalline state these complexes have imposed C2 symmetry, with cis-oxo/sulfido and trans-silyloxide ligands. 1H NMR spectra indicate that this stereoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…Burgmayer and coworkers also reported that compound (71) formed upon oxidation of salts of [Mo{S 2 C 2 (Ph)(2-quinoxalinyl)} 3 ] 2À [113]. Related reactions between MS 2 (OSiPh 3 ) 2 (Me 4 phen) (M = Mo (prepared in situ), W; Me 4 phen = 3,4,7,8-tetramethyl-1,10-phenanthrolene) and DMAC or PhCCPh yield M(S 2 C 2 R 2 )(OSiPh 3 ) 2 (Me 4 phen) (R = CO 2 Me, Ph, respectively) [137]. [138].…”
Section: Dithiolene-trispyrazolylborate Complexesmentioning
confidence: 99%
“…Burgmayer and coworkers also reported that compound (71) formed upon oxidation of salts of [Mo{S 2 C 2 (Ph)(2-quinoxalinyl)} 3 ] 2À [113]. Related reactions between MS 2 (OSiPh 3 ) 2 (Me 4 phen) (M = Mo (prepared in situ), W; Me 4 phen = 3,4,7,8-tetramethyl-1,10-phenanthrolene) and DMAC or PhCCPh yield M(S 2 C 2 R 2 )(OSiPh 3 ) 2 (Me 4 phen) (R = CO 2 Me, Ph, respectively) [137]. [138].…”
Section: Dithiolene-trispyrazolylborate Complexesmentioning
confidence: 99%
“…Bulky siloxy ligands are of interest as they can stabilize transition metal complexes with low coordination numbers, providing attractive structures and chemistry (Eppley et al, 1991;Neithamer et al, 1989;Huang & DeKock, 1993). The structural and reactivity studies of cis-M VI O 2 and cis-M VI OS complexes (M = Mo, W), including siloxy derivatives, are essential for understanding the activity of specific enzymes (Thapper et al, 1999;Miao et al, 2000). Both Mo VI O 2 and Mo siloxy derivatives have attracted attention as precursors, or as real catalytic species, in various catalytic applications (Heppekausen et al, 2012;Arzoumanian et al, 2008;Coelho et al, 2011;Bruno et al, 2006).…”
Section: Chemical Contextmentioning
confidence: 99%
“…[24][25][26][27][28][29] The nitrogen donor N8 is located trans to the terminal sulphido S1 with the relatively long W1-N8 bond (2.38-2.41 Å) most likely due to the structural trans effect of a multiple bonded sulphido ligand. 10,16,21,[30][31][32] Complexes 1S 2 and 4S 2 treated with diethyl acetylenedicarboxylate. (i) 1,2-C 2 H 4 Cl 2 , Lawesson's reagent, 60-80°C, 20 h (for 1S 2 -3S 2 ) (ii) 1,2-C 2 H 4 Cl 2 , P 2 S 5 , 20°C, 20 h (for 3S 2 and 4S 2 ).…”
Section: Synthesismentioning
confidence: 99%
“…Fig. 30 The compounds 1dt and 4dt are formally octahedral W(IV) complexes, so the metal centres may have either paramagnetic triplet or diamagnetic singlet d 2 electron configurations. Hydrogen atoms are omitted for clarity.…”
Section: Synthesismentioning
confidence: 99%